A Real Time Approach to Theft Prevention in the field of Transportation System - Mehta, Vartika; Punetha, Deepak; Bijalwan, Vishwanath (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
This paper report discusses a theft prevention system, which can prevent the theft and also can be track the object. This system is capable to tracking the vehicle as well as theft prevention. An R.F. module is use to exchange the information regarding vehicle and owner of the vehicle with police control room or SOS services. The vehicle can be track with the help of R.F. receiver. A DTMF based fuel lock has been attached in this system. A cell phone with SIM card has been attached with DTMF IC. The fuel flow in the vehicle can be controlled by give a call to this cell phone. This system has been controlled by a microcontroller which can make the system cost effective, low power consumption, effective and reliable.
Keywords: theft preventation; tracking; RF module; DTMF; microcontroller; mobile phone; IJIMAI